A brief history of the great Moghuls - Gascoigne, Bamber (Robinson, 2002)
Bamber Gascoigne's classic book tells of the most fascinating period of Indian history, the sixteenth and seventeenth centuries, when the country was ruled by the extraordinarily talented dynasty of emperors known to European travellers as 'the Great Moghuls', for their almost limitless power and incomparable wealth. Here is a unique picture of the way of life of India's most flamboyant rulers, their sublime palaces, their passions in art, science and religion, and their sophisticated system of administration that stabilized the greater part of India and was later adopted by the British. Acclaimed by travellers and scholars alike, and beautifully illustrated in colour with sixteen pages of photographs, this is a book for anyone with an interest in India's glorious past and an engaging survey of a splendid culture and its singular achievements.